Perspectives towards training approaches to skill achievement in swimming athletes: mixed methods - Ari Tri Fitrianto; Hegen Dadang Prayoga; Oddie Barnanda Rizky; Nina Sutresna; Albadi Sinulingga; Syahruddin Syahruddin; Trisnar Adi Prabowo (Physical Culture, Recreation and Rehabilitation)
Background and Study Aim. In recent years, the performance of swimming athletes in South Kalimantan Province has improved at the national level. The number of athletes in junior and student categories has also increased, and their average performance times have shown significant improvement. Therefore, further studies are needed to explore how coaches train swimming skills from the initial training stages to the development of athletes. This study aims to analyze the perspectives of swimming coaches on the training methods or approaches applied to athletes.